Analysis of the Clean and Healthy Lifestyle Program Implementation in the City of Mataram - Nurhasanah, Nurhasanah; Rachmayani, Ika; Suarta, I Nyoman; Arifamahira, Yumna (UPI Kampus Cibiru, 2024)
The Importance of Early Childhood Education (ECE) in shaping clean and healthy living behaviors. The health and cleanliness aspects of children are crucial elements in the formation of physical and spiritual development. Kindergartens (TK) are considered to have a central role in creating positive environments and habits related to cleanliness and health. However, evaluation results indicate that its implementation has not been optimal, especially after the COVID-19 pandemic period, precisely in the years 2023-2024. Understanding the urgency of this issue is paramount. Early childhood is a critical period for the establishment of lifelong habits, and the impact of health and cleanliness practices during this time resonates throughout one#39;s life. This research aims to shape and implement the PHBS program in the Selaparang district. The research method used is a quantitative research survey method. Respondents in this study consist of school principals. Data collection techniques in this study are through questionnaires and interviews. Based on the research results, it can be known that the form of PHBS program implementation consists of two main categories, namely personal hygiene and environmental cleanliness. The average final scores for the implementation of personal hygiene category (92%) and environmental cleanliness (96%) thus the overall average implementation (93%) falls under the category of excellent. thus showing that the PHBS program as a whole has been successfully implemented well. This has the potential to have a positive impact on the health and well-being of children in the kindergarten.